FACTORS AFFECTING ACCOUNTING CONSERVATISM IN CONSUMER GOODS COMPANIES IN INDONESIA STOCK EXCHANGE - Hadi, Arlia Natasya; Salim, Susanto (International Journal of Application on Economics and Business, 2023)
This study examines the relationship between accounting conservatism and leverage, capital intensity, profitability, dividend policy, and firm size in consumer goods non-cyclical companies listed on the Indonesia Stock Exchange between 2017 and 2019. In this research 87 observational data are used in which obtained from 29 consumer goods non-cyclical companies that have met established criteria, where the samples are selected using purposive sampling technique. Hypothesis testing in this study uses multiple regression analysis. The data were calculated and processed using Microsoft Excel 2013 dan EViews 12. This research tested the classical assumption before testing the hypothesis and used the multiple linear regression model method, which the suitable model for this research is Fixed Effect Model (FEM). The findings of this study show that accounting conservatism is significantly influenced by the variables of leverage and profitability, but not by the factors of capital intensity, dividend policy, or business size.